(untitled) (Issues in Social and Environmental Accounting (ISEA), 2025)
This paper visualises and demonstrates the application of the Catalyst, Enabler, and Enhancer (CEE) framework as a strategic model for managing stakeholder partnerships in higher education. This study employed a qualitative single-case study approach, analysing the strategic planning documents and performance reports of the Faculty of Accountancy (FPN) at Universiti Teknologi MARA (UiTM). This study maps the FPN’s operational initiatives to the three core roles of the CEE framework, i.e. catalyst, enabler and enhancer. This paper provides a replicable model for higher education institutions aiming to transform stakeholder engagement from supplementary activities into a driving force of institutional excellence and societal value.